Revisional Bariatric Surgery: Indications, Techniques and Outcomes - A Comprehensive Review - Jumaev N.A.; Teshaev O.R.; Juraev J.Z.; Lim I.I.; Gulomova M.J.; Kurbanov G.I. (International Journal of Medical Sciences And Clinical Research, 2025)
Background: Revisional bariatric surgery has emerged as a critical component of comprehensive obesity management, addressing inadequate weight loss, weight regain, and complications following primary bariatric procedures. Objective: This comprehensive review examines current evidence regarding indications, technical considerations, and outcomes of revisional bariatric surgery to guide clinical decision-making. Methods: A systematic review of contemporary literature was conducted, analyzing patient selection criteria, surgical techniques, complication rates, and long-term outcomes of revisional procedures. Results: Revision rates range from 10-25% over 10 years, with adjustable gastric band procedures demonstrating the highest revision requirements (30-60%). Revisional surgery achieves 40-70% excess weight loss (%EWL), though outcomes remain inferior to primary procedures. Complication rates are elevated (15-30% overall morbidity, 0.5-2% mortality) compared to primary operations. Conclusions: Revisional bariatric surgery can provide meaningful benefits for appropriately selected patients but requires careful risk-benefit assessment. Optimal outcomes depend on thorough preoperative evaluation, experienced surgical technique, and comprehensive long-term follow-up.